Studying the Relationship between Lack of Job Promotion and Career Plateau of Staff: A Case Study in Well Being Office of Kerman - Vahid Azodi; Ma'soumeh Dehghani; Ali Hamedani; Hadi Shafiee (International Journal of Management, Accounting and Economics, 2016)
Behavior of staff in an office or organization can be affected by their job attitudes. Therefore, it is necessary that managers be aware of them. The present research aims to study the effect of lack of job promotion of well-being staff of Kerman on their job motivations. The method used in this research is descriptive survey. Statistical population of the research is 80 persons including official, contractual staff in well-being of Kerman city. The present research is correlative and data and information were gathered by field researches (questionnaire) with complete census sampling. Results show that staff under the consideration are exposed to lack of job motivation due to their type of job so that managers require identifying this issue accurately. Also, results indicated that if staff have positive attitudes towards their jobs, they will expose to fewer plateaus. As a result, managers of well-being organization should try to increases positive attitudes of the staff.